2001
DOI: 10.1016/s0006-3495(01)76070-5
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Induced Proton Transport of Pharaonis Phoborhodopsin (Sensory Rhodopsin II) Is Ceased by Association with the Transducer

Abstract: Phoborhodopsin (pR; also sensory rhodopsin II, sRII) is a retinoid protein in Halobacterium salinarum and works as a receptor of negative phototaxis. Pharaonis phoborhodopsin (ppR; also pharaonis sensory rhodopsin II, psRII) is a corresponding protein of Natronobacterium pharaonis. In bacterial membrane, ppR forms a complex with its transducer pHtrII, and this complex transmits the light signal to the sensory system in the cytoplasm. We expressed pHtrII-free ppR or ppR-pHtrII complex in H. salinarum Pho81/wr(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
115
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 38 publications
4
115
0
Order By: Relevance
“…In contrast, sensory rhodopsins SRI and SRII have slow photocycles (20,31,48), which allows the transient accumulation of long lived signaling states of the receptors to catalyze a sustained phosphorylation cascade controlling flagellar motor rotation (49). The fast photocycle of MR is therefore similar to those of ion pumping rhodopsins from other sources.…”
Section: Photocycles Of Mr and Hwbr As Revealed By Ftir And Time-resomentioning
confidence: 99%
“…In contrast, sensory rhodopsins SRI and SRII have slow photocycles (20,31,48), which allows the transient accumulation of long lived signaling states of the receptors to catalyze a sustained phosphorylation cascade controlling flagellar motor rotation (49). The fast photocycle of MR is therefore similar to those of ion pumping rhodopsins from other sources.…”
Section: Photocycles Of Mr and Hwbr As Revealed By Ftir And Time-resomentioning
confidence: 99%
“…On formation of the NpSRII/NpHtrII complex this function is inhibited 22,23 . This inhibition may originate from kinetics alteration, from structural changes prohibiting the pumping, or from combination of these factors.…”
Section: Implications For Npsrii Proton Pumpingmentioning
confidence: 99%
“…A second observation relates to the inhibition of the proton pump on transducer binding NpHtrII to its cognate receptor NpSRII 22,23 . It has been discussed that in the 2:2 complex the cytoplasmic channel cannot open sufficiently, thereby altering the proton uptake kinetics such that the reprotonation of the Schiff base is faster from the extracellular side.…”
Section: Introductionmentioning
confidence: 99%
“…Photocycle kinetics in the detergent-solubilized SRII-HtrII complex was measured by Sudo et al (15), who concluded that the decay of the M intermediate is slowed in the presence of transducer. On the other hand, no change in the photocycle rate was observed for the same complex reconstituted in lipids (16,17). Measurements of transient voltage and pH changes in membranes containing transducerfree SRII demonstrated that the receptor (but not the receptortransducer complex) functions as a light-driven proton pump, although with less efficiency than BR (17,18).…”
mentioning
confidence: 93%